Assessment of BRAF V600E mutation status by immunohistochemistry with a mutation-specific monoclonal antibody - Capper, David; Preusser, Matthias; Habel, Antje; Sahm, Felix; Ackermann, Ulrike; Schindler, Genevieve; Pusch, Stefan; Mechtersheimer, Gunhild; Zentgraf, Hanswalter; Deimling, Andreas von (Acta neuropathologica, 2011)
Activating mutations of the serine threonine kinase v-RAF murine sarcoma viral oncogene homolog B1 (BRAF) are frequent in benign and malignant human tumors and are emerging as an important biomarker. Over 95% of BRAF mutations are of the V600E type and specific small molecular inhibitors are currently under pre-clinical or clinical investigation. BRAF mutation status is determined by DNA-based methods, most commonly by sequencing. Here we describe the development of a monoclonal BRAF V600E mutation-specific antibody that can differentiate BRAF V600E and wild type protein in routinely processed formalin-fixed and paraffin-embedded tissue. A total of 47 intracerebral melanoma metastases and 21 primary papillary thyroid carcinomas were evaluated by direct sequencing of BRAF and by immunohistochemistry using the BRAF V600E mutation-specific antibody clone VE1. Correlation of VE1 immunohistochemistry and BRAF sequencing revealed a perfect match for both papillary thyroid carcinomas and melanoma metastases. The staining intensity in BRAF V600E mutated tumor samples ranged from weak to strong. The generally homogenous VE1 staining patterns argue against a clonal heterogeneity of the tumors investigated. Caution is essential when only poorly preserved tissue is available for VE1 immunohistochemical analysis or when tissues with only little total BRAF protein are analyzed. Immunohistochemistry using antibody VE1 may substantially facilitate molecular analysis of BRAF V600E status for diagnostic, prognostic, and predictive purposes.